First Reported Case of MitraClip Placement Due to Mitral Valve Flail in the Setting of Cardiac Amyloidosis. (August 2016) - Krishnaswamy, Amar; Hanna, Mazen; Goodman, Andrew; Kapadia, Samir R.
Abstract : Supplemental Digital Content is available in the text.